Wplyw dlugotrwalego wyczynowego treningu fizycznego na stan napiecia ukladu wegetatywnego okreslonego zmiennoscia rytmu zatokowego - Sielanczyk, A.; Jagidzinski, L.; Gmyrek, J.; Niepsuj, K. J. (Medycyna sportowa, 2001)
Heart rate variability (HRV) is one of the methods which helps to estimate the influence of the sympathetical system on the heart. The influence of long-term physical exercise on the sympathetical tonus determined by HRV, taking into consideration different sporting games was the aim of this study. In our study 38 men were analyzed. The examined group consisted of 21 sportsmen; 7 basketball players - subgroup A and 14 footballers - subgroup B. The control group consisted of 17 healthy volunteers. All 38 men had their HRV examined in standard conditions. An increase of pBB 50 in the group of sportsmen compared to the control group was noticed. Subgroup A was compared with B and both of them with the control group. No statistical significance between the control group and subgroup B was shown. Statistical significance in SD 5-9, HRV index and pBB 50 between subgroup B and the control group, as well as between subgroup A and B was observed.